Adsorption of mercury(ii) from water by a novel sPAN fiber containing sulfhydryl, carboxyl and amino groups. Issue 67 (14th November 2018) - Duan, Wenjie; Wang, Jing; Chang, Li; Zhao, Liang; Tian, Zhenbang; Huang, Zuohua; Huang, Weiqing
Abstract : A novel fiber containing sulfhydryl, carboxyl and amino groups (sPAN) with high adsorption capacity for mercury was facilely prepared by chemically grafting cysteine onto a commercial polyacrylonitrile (PAN) fiber in a one-step reaction. Abstract : A novel fiber containing sulfhydryl, carboxyl and amino groups (sPAN) with high adsorption capacity for mercury was facilely prepared by chemically grafting cysteine onto a commercial polyacrylonitrile (PAN) fiber in a one-step reaction. The as-prepared sPAN was characterized for its chemical structure, thermal stability, tensile strength, surface morphology and surface binding species. The adsorption and desorption performances for mercury were investigated by both batch and dynamic experiments. The results showed that sPAN was effective for mercury removal over pH 4–7, and ionic strength produced no obvious interference with the adsorption. The equilibrium adsorption capacity of mercury could be as high as 459.3 (±16.0) mg g −1, much higher than for most previously reported materials due to the strong interaction between mercury ions and sulfhydryl, carboxyl, amino groups. More than 99% adsorbed mercury could be eluted by the mixture of hydrochloric acid and thiourea, and the regenerated sPAN could be reused for mercury removal with no significant loss of adsorption capacity even after 10 cycles. The dynamic adsorption results indicated that at initial mercury concentrations of 0.1 and 1.0 mg L −1, the residual mercury concentration was less than 1 μg L −1, which could meet the criterion for drinking water. Moreover, at an initial mercury concentration of 10 mg L −1, the residual mercury concentration was less than 50 μg L −1, which could satisfy the Chinese national industry water discharge standard.